Proceedings of the 9th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2017
DOI: 10.1145/3122986.3122997
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Touch and Pressure-Based Scrolling and Haptic Feedback for In-Car Touchscreens

Abstract: An in-car study was conducted to examine different input techniques for list-based scrolling tasks and the effectiveness of haptic feedback for in-car touchscreens. The use of physical switchgear on centre consoles is decreasing which allows designers to develop new ways to interact with incar applications. However, these new methods need to be evaluated to ensure they are usable. Therefore, three input techniques were tested: direct scrolling, pressure-based scrolling and scrolling using onscreen buttons on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…through vibrotactile feedback, force feedback, or non-speech audio to augment the kinesthetic sense [43]. Such feedback mechanisms have been considered in other contexts such as in-car interactions, in which users do not always have a direct line of sight to the input controls [42].…”
Section: Implications For Tangible Self-report Researchmentioning
confidence: 99%
“…through vibrotactile feedback, force feedback, or non-speech audio to augment the kinesthetic sense [43]. Such feedback mechanisms have been considered in other contexts such as in-car interactions, in which users do not always have a direct line of sight to the input controls [42].…”
Section: Implications For Tangible Self-report Researchmentioning
confidence: 99%
“…Several related studies have reported that haptic feedback improves the response time and performance [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In particular, in environments requiring visual attention such as driving, lack of haptic feedback could considerably hinder safety, making such critical feedback [ 10 , 20 , 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…However, the noise vibration applied in Collins et al’s study used digitally generated quasi-white noise, and it was an experiment to see how the noise affected the detection threshold when the intensity of the haptic stimulation was smaller or larger than the threshold. Besides, Ng et al conducted experiments on the accuracy of operation during actual vehicle driving, for experiments under the driving environment [ 17 ]. However, Ng et al noted that there was a limitation because the haptic stimulation was not sufficiently large compared to the driving vibration, and their experiments were not to find the detection threshold.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, mobile devices can lead to motion sickness when users look down onto the 1 e.g., BMW 7 series, www.bmw.de/7er, last accessed: 2019-06-20 screen instead of looking in the direction of movement [5]. Furthermore, the use of direct touch in a car can reduce accuracy [13], needs more eye-glances [4], and increases task completion times compared to traditional buttons [13]. For the driver, this also negatively affects vehicle guidance and driving safety while interacting with the system [18].…”
Section: Introductionmentioning
confidence: 99%